2016
DOI: 10.1007/s10903-016-0530-z
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Status of Double Minority Adolescents: Findings from National Cross-Sectional Health Surveys

Abstract: Background: Little population-based work has been published about the mental health

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…Chinese and sexual/gender minority identities were described as integral parts of As detailed previously, the presence of strong cultural and family ties (Snowshoe et al 2017;Reid et al 2016), as well as personal resilience (LeVasseur, Kelvin and Grosskopf 2013) developed over many years, could help to explain why Chinese sexual/gender minority youth in New Zealand may be more equipped to manage psycho-social challenges than their New Zealand European counterparts (Chiang et al 2017). Similar findings emerged from studies on Taiwanese and Hispanic sexual minority men in the USA (Rios and Eaton 2016;Wang, Bih and Brennan 2009), indicating that these men may develop an alternative path to obtain parental support and create additional supporting social networks while being marginalised.…”
Section: Intersectional Challengesmentioning
confidence: 95%
See 1 more Smart Citation
“…Chinese and sexual/gender minority identities were described as integral parts of As detailed previously, the presence of strong cultural and family ties (Snowshoe et al 2017;Reid et al 2016), as well as personal resilience (LeVasseur, Kelvin and Grosskopf 2013) developed over many years, could help to explain why Chinese sexual/gender minority youth in New Zealand may be more equipped to manage psycho-social challenges than their New Zealand European counterparts (Chiang et al 2017). Similar findings emerged from studies on Taiwanese and Hispanic sexual minority men in the USA (Rios and Eaton 2016;Wang, Bih and Brennan 2009), indicating that these men may develop an alternative path to obtain parental support and create additional supporting social networks while being marginalised.…”
Section: Intersectional Challengesmentioning
confidence: 95%
“…self-advocacy when facing mistreatment and oppression, and the development of alternative social support networks (Li et al 2017;Rios and Eaton 2016). Indeed, our recent New Zealand study (Chiang et al 2017) found that while sexual/gender and ethnic minority status were singularly more likely to be associated with mental illhealth, double minority youth were overall less likely to report mental ill-health than their ethnic-majority (i.e., New Zealand European) sexual/gender minority peers.…”
Section: Introductionmentioning
confidence: 90%
“…This in turn can lead to self-loathing and a range of unhelpful cognitions, which are then thought to place LGBT+ young people at greater risk of mental health problems, such as depression [6]. Moreover, it is not unusual for LGBT+ young people to face the challenge of navigating multiple stigmas related to difference, such as being LGBT+ and having mental health problems [7] or being an ethnic minority and LGBT+ [8]. In addition to being different and having greater mental health needs,…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of psychology, the optimal status of adolescents' mental health is the maximization of positive emotions, and sports training is the most influential way for adolescents' emotional benefits (Tan, Chen, Xia et al, 2017). From the perspective of sports psychology, sports can change people's negative emotions, effectively improve their mood, and reduce depression and anxiety (Chiang, Fleming, Lucassen et al, 2017). Continuous sports training can change the cognitive pattern and lifestyle of adolescents, educate them with a wider range of resources such as physical, cognitive, psychological and social knowledges, ultimately, it can cultivate the adolescents to form sports training habits and awareness of continuous sports training (Harikrishnan, Arif, & Sobhana, 2017, Shulman, Luo, & Shah, 2018.…”
Section: Introductionmentioning
confidence: 99%